Color and texture in weaving : 150 contemporary designs - Selby, Margo (Interweave, 2011)
"Learn to create textiles that are rich with color and texture. Using either a simple four- or eight-shaft loom, you can discover how to mix color and yarn types in your weaving with Color and Texture in Weaving."--P. [4] of cover.